NO MUSHY ZONES IN THE EARTH'S CORE - Morse S.A. (My University, 2002)
Mushy zones, assemblages of crystals and their pore-space liquids, have been invoked for both the upper and lower boundaries of the liquid outer core. The timescale of very slow accumulation compared with solidification at either of these interfaces militates against such zones, where instead hard ground should be expected to form by solidification at the interface. Such adcumulus growth involves isothermal, isocompositional solidification by successful exchange of evolving solute with fresh melt from an infinite reservoir. At both boundaries of the outer core, the removal of rejected material is significantly aided by compositional convection. The accumulation rates at the outer core boundaries are orders of magnitude slower than required for adcumulus growth, as calibrated both by field and experimental evidence in silicate melts. A conceptual phase diagram for the core-mantle boundary helps to visualize the relevant equilibria. Capture of core metal into the mantle has been suggested to occur via a mushy zone, to explain a high electrical conductivity there, as plausibly required by the secular behavior of the Earth's nutation. One conjecture is that the rejected light elements from the freezing of the inner core might be able to congregate as a porous flotation sediment at the top of the core. The idea of porosity in such a mushy zone must be rejected from experience with solidification of cumulates from magmas.A high electrical conductivity might instead be caused by solution of core metal by mantle, followed by exsolution. The hottest part of the mantle lies in contact with the molten outer core, where the maximum solubility of Fe must occur in the major mantle phases. On leaving the core-mantle boundary, the mantle must cool and may exsolve metal on the metal-silicate solvus. If the iron-rich metal resides chiefly in the rheologically weaker metal oxide phase, which coats the deforming perovskite grains, it may furnish a short circuit for mantle conductivity in the basal mantle. At still cooler and higher levels, the mantle encounters more normal mantle redox conditions, and any exsolved Fe metal should oxidize to FeO in the metal oxide and perovskite phases, ceasing to be a conductor.